Pengaruh kompetensi, pengetahuan etika profesi, dan audit fee terhadap kualitas kinerja auditor - Jhlavaro Xevindorhot Gilest; Maulana Malik Muhammad; Donant Alananto Iskandar (LPMP Imperium, 2025)
The research aimed to examine the influence of competence, ethical knowledge of the auditing profession, and audit fees on the quality of audit performance at public accounting offices in the province of DKI Jakarta. A random sampling method was employed, utilizing questionnaires as the data collection instrument. The study involved 105 respondents, all auditors working in public accounting offices in DKI Jakarta. The data collected through the distribution of the questionnaires were processed using SPSS software version 26. The research results indicate that competence, knowledge of ethics in the auditing profession, and audit fees significantly influence the quality of auditor performance.